1990
DOI: 10.1073/pnas.87.5.1735
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids enhance the binding of peptides to class II major histocompatibility molecules.

Abstract: The binding of a lysozyme and ovalbumin peptide to purified class II major histocompatibiity molecules in detergents was increased by the addition of certain lipids. Natural lipids from B lymphoma cells enhanced the binding and so did phosphatidylcholine, phosphatidylserine, phosphatidylinositol, and cardiolipin. Phosphatidylethanolamine, sphingomyelin, and cholesterol had no effect. There was no major difference between the effects of a phospholipid and its lyso derivative. As studied with phosphatidylcholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
30
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 40 publications
3
30
1
Order By: Relevance
“…The major goal of these attempts is to deliver high amounts of immunogenic peptide antigens derived from tumor-specific or tumor-associated proteins. In addition to the benefit of increased loading rates, these small molecular catalysts would also allow the bypassing of proteolytic endosomal processing compartments, which facilitates the presentation of epitopes sensitive to proteolytic degradation when following the classical MHC class II presentation pathway.Previous studies have already shown that, under certain conditions, the stability of peptide-MHC complexes can be affected by detergents or detergent-like compounds (16,17). The mechanism, however, remained obscure, and the chemical nature of these compounds did not allow any experiments with…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The major goal of these attempts is to deliver high amounts of immunogenic peptide antigens derived from tumor-specific or tumor-associated proteins. In addition to the benefit of increased loading rates, these small molecular catalysts would also allow the bypassing of proteolytic endosomal processing compartments, which facilitates the presentation of epitopes sensitive to proteolytic degradation when following the classical MHC class II presentation pathway.Previous studies have already shown that, under certain conditions, the stability of peptide-MHC complexes can be affected by detergents or detergent-like compounds (16,17). The mechanism, however, remained obscure, and the chemical nature of these compounds did not allow any experiments with…”
mentioning
confidence: 99%
“…Previous studies have already shown that, under certain conditions, the stability of peptide-MHC complexes can be affected by detergents or detergent-like compounds (16,17). The mechanism, however, remained obscure, and the chemical nature of these compounds did not allow any experiments with living cells.…”
mentioning
confidence: 99%
“…32 Though cell division and proliferation was not affected as evaluated using the method proposed by Mourant et al, 33 increased survival indicated that AHP/NAHP influenced the metabolic pathways of PBMCs. We show that plasma factors influence the biogenesis of phospholipids (which are essential membrane components) that are required for normal functioning of APCs, as these are involved in processes like endocytosis, 39 autophagy, [40][41][42] and antigen processing and presentation. 43 Lipids are important components of lipid rafts that are essential for many cellular processes like transport and insertion of membrane proteins that can alter the structure and function of the immune cells and can lead to disease conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Different MHC alleles bind varying spectra of peptides, and a given peptide will generally bind only to a subset of MHC alleles. The presentation of and immune response to a peptide is, accordingly, "restricted" to these alleles, and this may explain the fact that increased risk of various autoimmune disorders is restricted to particular MHC genotypes Todd et al, 1988 (Roof et aL., 1990). Binding kinetics indicate that only 1 00/o-600/o of purified MHC-11 can bind peptides in vitro, a reflection of denaturation, occupation by other peptides, or the presence of different MHC-11 conformers that vary in their binding affinities.…”
mentioning
confidence: 99%
“…Peptides bind to MHC-11 molecules in a saturable and homogeneous binding reaction with binding affinities in the micromolar range (Babbitt et aL, 1985). The binding is characterized by a slow on-rate and by a very slow rate of dissociation (Buus et al, 1986;Allen et al, 1989;SadeghNasseri and McConnell, 1989;Roof et al, 1990). Some peptides, once bound, will practically not dissociate unless the MHC-11 molecules are drastically denatured.…”
mentioning
confidence: 99%